2021
DOI: 10.3390/ijms22020839
|View full text |Cite
|
Sign up to set email alerts
|

Varied Expression of Senescence-Associated and Ethylene-Related Genes during Postharvest Storage of Brassica Vegetables

Abstract: The genus Brassica comprises a highly diverse range of vegetable crops varying in morphology, harvestable crop product, and postharvest shelf-life that has arisen through domestication, artificial selection and plant breeding. Previous postharvest studies on the shelf-life of Brassica species has mainly focused on the variable rates of physiological changes including respiration and transpiration. Therefore, further understanding of the molecular basis of postharvest senescence in Brassica vegetables is needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…As previously explained, low storage temperatures over the optimum product storage temperature (0–2 °C for broccoli) are interpreted by plant cells as abiotic stresses . Hence, the expression of ACC oxidase genes and its activity were induced by low temperatures in broccoli from 22 to 4 °C . Lelièvre et al observed similar results in pears reporting that ACC synthase gene expression is regulated under chilling temperatures, while ACO gene expression can be activated distinctly by either chilling or ethylene.…”
Section: Results and Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…As previously explained, low storage temperatures over the optimum product storage temperature (0–2 °C for broccoli) are interpreted by plant cells as abiotic stresses . Hence, the expression of ACC oxidase genes and its activity were induced by low temperatures in broccoli from 22 to 4 °C . Lelièvre et al observed similar results in pears reporting that ACC synthase gene expression is regulated under chilling temperatures, while ACO gene expression can be activated distinctly by either chilling or ethylene.…”
Section: Results and Discussionmentioning
confidence: 60%
“…49 Hence, the expression of ACC oxidase genes and its activity were induced by low temperatures in broccoli from 22 to 4 °C. 52 Lelievre et al 53 observed similar results in pears reporting that ACC synthase gene expression is regulated under chilling temperatures, while ACO gene expression can be activated distinctly by either chilling or ethylene.…”
Section: Validation Of the Effect Of Released Eos From Active Packagi...mentioning
confidence: 73%
See 1 more Smart Citation
“…When these substrates are utilized and completely oxidized, different amounts of oxygen are consumed concerning the amount of CO 2 evolved [56]. By knowing that starch hydrolysis starts during fruit ripening and storage [57][58][59], we can indisputably assert that the lower detected TSS values of coated apples rather than uncoated samples can be ascribed to the slower respiration process, being also corroborated by the previously shown results of Figure 1b, which demonstrate the lower total sugar content in apples' tissue.…”
Section: Tss Ta Ph and Vitamin Cmentioning
confidence: 99%
“…It has been reported that during the progression of senescence, certain SAGs are upregulated or downregulated. With regard to the ethylene-related genes, it has been reported that some are barely detectable in freshly harvested immature florets ( BoACO2 and BoACO3 ), while others like BoACO3 are only expressed in whole yellow florets (Ahlawat and Liu, 2021). There are also other examples of broccoli genes that exhibit different expression patterns after harvest and through senescence; for example, BoACS1 (DNA clone of ACC synthase) had high transcript levels after harvest but was not detected during storage.…”
Section: Introductionmentioning
confidence: 99%